Comparison of Ananda Mother and Child Hospital (RSIA) and St. Khadijah 1 Mother and Child Hospital in Terms of Marketing Strategy, Patient Culture, and Maternity Care Interest (RSIA) Muhammadiyah Makassar - Azharatul Jannah; Irwandy Irwandy; Syahrir A. Pasinringi; M. Alimin Maidin; Noer Bahry Noor; Nasruddin Nasruddin (Journal of Community Health Provision, 2022)
Interest in making a purchase results from a combination of factors, including exposure to advertising, familiarity with the brand, familiarity with the product itself, and an examination of alternative methods of achieving the same goal. Marketing and societal pressures are examples of such outside forces. Comparing the marketing strategies, societal norms, and patient interest between RSIA St.Khadijah 1 Makassar and RSIA Ananda Mother and Child Hospital in Makassar is the focus of this research. This study is a quantitative observational study employing a cross-sectional study design. Univariate, multivariate, and bivariate analyses were applied to the data. Patients in the ob-gyn clinics at RSIA Ananda and RSIA St. Khadijah 1 in Makassar made up the bulk of the 187 participants in this study. The research found that RSIA Ananda and RSIA St.Khadijah had different marketing strategies, societal norms, and patient priorities. Managing, empowering, and evaluating the 7 parts of the marketing mix and social culture at RSIA Ananda and RSIA St.Khadijah jointly is recommended to the management.